PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 56 PEKANBARU - Erlisnawati Erlisnawati; Hendri Marhadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
The problem on this researchis is that low students’ achievement on social science in fourthgraderes at SD Negeri 56 Pekanbaru within average score 60 and clasical completenes 40%within minimal completenes criterion stated is 70. The purpose of this research is to improvestudents’ achievement on social science of the fourth graderes in SD Negeri 56 Pekanbaruwith the application of cooperative learning model type Group Investigation. This researchwas classroom action research consisting 2 cycles within 4 procedures: planning, doing,observing, and reflecting, and each cycle consists of three meetings. Instruments on thisresearch are sylabus, lesson plan, and student work sheet. Instruments for collecting data areobservation sheet and test. Data which was collected were learning outcomes and teacher’sactivities during the lessons. After impelentation of cooperatif learning model type GroupInvestigation it was abtained students’ outcomes in UH I within average 70,50 (improvedfrom basic score 17,50%) with classicall completeness 60%. The average score form UH IIwas 80,83 (improved 34,72%) with classicall completeness 81,82%. Teacher activities resultsin the first meeting of the first cycle was 59,38% (fair category), 71,88% (good category) forthe second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 84,38%(very good category), 90,63% (very good category) for second meeting in cycle II. Students’activity in the first meeting of the cycle I was 56,25% 9fair category), 65,63% (goodcategory) ) for the second meeting in cycle I. And then in the first meeting of the secondcycle was 81,25% (very good category), 87,50% (very good category) for second meeting incycle II. Based on this result it can be concluded that the implementation of cooperatiflearning model type Group Investigation can social science in fourth graderes at SD Negeri56 Pekanbaru.Keywords: Cooperatif Group Investigation, Students Achievement the Result Of SocialStudies